2014
DOI: 10.1007/s12010-014-0928-9
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Lipopeptide Biosurfactant from Thermophilic Bacterium Aneurinibacillus thermoaerophilus MK01 Newly Isolated from Municipal Landfill Site

Abstract: A biosurfactant-producing thermophile was isolated from the Kahrizak landfill of Tehran and identified as a bacterium belonging to the genus Aneurinibacillus. A thermostable lipopeptide-type biosurfactant was purified from the culture medium of this bacterium and showed stability in the temperature range of 20-90 °C and pH range of 5-10. The produced biosurfactant could reduce the surface tension of water from 72 to 43 mN/m with a CMC of 1.21 mg/mL. The strain growing at a temperature of 45 °C produces a subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Lipopeptide produced by MSA31 was found to be thermostable as revealed by DSC analysis. Similar thermostable lipopeptide were produced by Nocardiopsis sp ., Brevibacterium aureum , and Aneurinibacillus thermoaerophilus MK01 (Gandhimathi et al, 2009; Kiran et al, 2010b; Sharafi et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Lipopeptide produced by MSA31 was found to be thermostable as revealed by DSC analysis. Similar thermostable lipopeptide were produced by Nocardiopsis sp ., Brevibacterium aureum , and Aneurinibacillus thermoaerophilus MK01 (Gandhimathi et al, 2009; Kiran et al, 2010b; Sharafi et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…From the biological, biochemical, and structural point of view, the most biosurfactants are complex molecules comprising different structures. Here, they are represented in the following groups: (1) glycolipids, (2) lipopeptides and lipoproteins, (3) polysaccharide protein complex, (4) fatty acids, (5) phospholipids, and (6) polymeric biosurfactants . Other combination of these groups like glycolipopeptide and lipopolysaccharide also exist.…”
Section: Introductionmentioning
confidence: 99%
“…For Bacillus brevis, this was 71.89 ± 0.56% with crude oil (Mouafi et al, 2016). The stability of MSI 54 was higher than that reported Sharafi et al, 2014;Jha et al, 2016). The MSI 54 lipopeptide effectively remediated heavy metals such as mercury, lead, cadmium, and manganese at 2.0 × CMC.…”
Section: Discussionmentioning
confidence: 87%
“…Stability studies showed that the activity of the MSI 54 biosurfactant was not affected at higher temperature, pH, and salt concentrations, suggesting its environmental applications such as heavy metal remediation and metal recovery from the complex using ultrafiltration (Ferella et al, 2007). Several lipopeptide biosurfactants from marine sponge-associated bacteria have been reported Kiran et al, 2010bKiran et al, , 2017Sharafi et al, 2014). However, the MSI 54 lipopeptide biosurfactant seems to be unique based on GC-MS analysis; its stability and emulsification index were found to be higher than those reported.…”
Section: Discussionmentioning
confidence: 89%